(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2026)
The process of career development spans from childhood through adulthood, influenced by parental involvement, academic experiences, and personal aspirations, with a focus on aligning individual interests and strengths to foster purposeful career decisions, highlighting the crucial role of parental guidance and the need for a comprehensive understanding of parental influence on career development. This study aims to determine the correlates between parental involvement and career development among the respondents. The study utilized a descriptive correlational research design to explore the relationship between variables, focusing on the level of independence of Senior High School students and parental involvement in their career development, with data collected through validated surveys and qualitative insights from open-ended questionnaires administered to both students and parents, analyzed using descriptive statistics, Analysis of Variance (ANOVA), and qualitative analysis techniques. Findings revealed that students generally have a high degree of independence when it comes to making decisions about their education and training as well as goal-setting. In addition, parental involvement is emphasized, highlighting the important role parents play in assisting their children in making career decisions. There is also no significant difference between parent’s highest educational attainment and occupation. This study underscore the significant influence of parental involvement on students’ career decisions despite their high level of independence, emphasizing the crucial role parents play in guiding their children’s career paths, with no notable disparity found between parental educational attainment and occupation. The results were the baseline for designing a brochure for career guidance programs tailored to help the needs of the students.